Irradiance dependency of oxidative stress and coral bleaching - Michael P. Lesser (Coral Reefs, 2024)

Reply to Kahng, S.E. Comment on “Lesser et al. Using Stable Isotope Analyses to Assess the Trophic Ecology of Scleractinian Corals. Oceans 2022, 3, 527–546” - Michael P. Lesser; Marc Slattery; Keir J. Macartney (Oceans, 2024)
Kahng [...]

Function and stability of mesophotic coral reefs - Marc Slattery; Michael P. Lesser; Luiz A. Rocha; Heather L. Spalding; Tyler B. Smith (Trends in Ecology & Evolution, 2024)

Correction: Quantifying sponge communities from shallow to mesophotic depths using orthorectified imagery - Michael P. Lesser; Marc Slattery; Keir J. Macartney (Marine Biology, 2024)